Comparison of thalidomide and lenalidomide as therapy for myelofibrosis - Jabbour, Elias (American Society of Hematology, 2011)
With the use of the International Working Group for Myelofibrosis Treatment and Research consensus criteria, we re-assessed the efficacy of thalidomide and lenalidomide in 125 patients with myelofibrosis treated in 3 consecutive phase 2 trials: 44 received single-agent thalidomide, 41 single-agent lenalidomide, and 40 a combination of lenalidomide plus prednisone. The thalidomide group included significantly more untreated patients and patients with performance status of 2. The Lenalidomide-based therapy produced higher efficacy (34%-38%) than thalidomide (16%; P = .06). Responses to thalidomide were seen within 3-15 weeks, whereas responses to the lenalidomide-based therapy were also seen after a prolonged course of therapy (range, 2-45 weeks). Lenalidomide plus prednisone therapy resulted in significantly longer response duration (median, 34 months) than single-agent lenalidomide or thalidomide (median, 7 and 13 months, respectively; P = .042). Fewer patients (P = .001) discontinued the lenalidomide plus prednisone therapy (13%) because of side effects then patients on single-agents therapy (32%-39%). In conclusion, the combination of lenalidomide plus prednisone appears to be more ef-fective and safer than single-agent thalidomide or lenalidomide.